Incorporating phylogenetic uncertainty on phylogeny-based palaeontological dating and the timing of turtle diversification - Sterli, Juliana (2012)
Methods improving the performance of molecular dating of divergence time of clades have improved dramatically in recent years. The calibration of molecular dating using the first appearance of a clade in the fossil record is a crucial step towards inferring the minimal diversification time of various groups and the choice of extinct taxa can strongly influence the molecular dates. Here, we evaluate the uncertainty on the phylogenetic position of extinct taxa through non-parametric bootstrapping. The recognition of phylogenetic uncertainty resulted in the definition of the Bootstrap Uncertainty Range (BUR) for the age of first appearance of a given clade. The BUR is calculated as the interval of geological time in which the diversification of a given clade can be inferred to have occurred, based on the temporal information of the fossil record and the topologies of the bootstrap trees. Divergence times based on BUR analyses were calculated for three clades of turtles: Testudines, Pleurodira and Cryptodira. This resulted in extensive uncertainty ranges of topology-dependent minimal divergence dates for these clades.